1993
DOI: 10.1002/jbmr.5650081205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between quadriceps strength and bone mineral density of the proximal tibia and distal forearm in women

Abstract: It is well known that there is a relationship between muscle strength and bone density, but it is uncertain whether this relationship is site specific. The aim of this study was to assess the relationship of quadriceps strength to site-specific bone mineral density (BMD) of the tibia and to BMD of the forearm. In 66 healthy women, aged 21-78 years, BMD was measured in the proximal tibia and the distal forearm by dual-photon absorptiometry. Isometric and isokinetic strength of the quadriceps was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 17 publications
0
16
1
1
Order By: Relevance
“…Our population, enriched with overweight and obese subjects, allowed examination of the relationship between L-LBM, knee extensor strength, and BMD in these heavier groups, which is important because these factors are also associated with higher BMI. Although prior studies of healthy women demonstrated a relationship between BMD and knee extensor strength, (21,32) to our knowledge, the finding that knee extensor strength is not a significant predictor of BMD in obese adults has not been reported previously. This finding may indicate that increased body weight sufficiently loads the skeleton to maintain higher hip BMD in obese adults, whereas loading by the pull of the knee extensors is a more significant contributor to maintaining higher BMD in non-obese adults.…”
Section: Discussioncontrasting
confidence: 54%
“…Our population, enriched with overweight and obese subjects, allowed examination of the relationship between L-LBM, knee extensor strength, and BMD in these heavier groups, which is important because these factors are also associated with higher BMI. Although prior studies of healthy women demonstrated a relationship between BMD and knee extensor strength, (21,32) to our knowledge, the finding that knee extensor strength is not a significant predictor of BMD in obese adults has not been reported previously. This finding may indicate that increased body weight sufficiently loads the skeleton to maintain higher hip BMD in obese adults, whereas loading by the pull of the knee extensors is a more significant contributor to maintaining higher BMD in non-obese adults.…”
Section: Discussioncontrasting
confidence: 54%
“…Still, athletes exhibiting higher bone impact usually show higher BMD values. As a result, BMD values in such athletes are generally higher unless notable discrepancies such as the female athlete triad 15,16 and other risk factors are seen for a prolonged period.…”
mentioning
confidence: 99%
“…The spectrum of low energy availability, amenorrhea, and osteoporosis, either alone or in combination, are regarded as significant health risks for female athletes and are medically referred to as "the female triad." 15,16 Female athletes who participate in gymnastics, track, diving, dance, and synchronized swimming are affected most frequently. 1 Supporting this idea, women who exercise and maintain normal menstrual cycles seem to have higher BMD than amenorrheic women.…”
mentioning
confidence: 99%
“…Some studies have also demonstrated that higher loads at specific sites provided a more effective osteogenic stimulus than generally distributed loading at a lower intensity [33]. However, although a positive effect of physical activity on BMD has been reported by some authors [30,34,35], specific resistive loading beyond which bone is normally loaded during activities of daily living is usually required to achieve these effects [33]. This may explain why we did not find significant differences in BMD between our groups.…”
Section: Discussionmentioning
confidence: 52%